The impossible process: Thermodynamic reversibility. (August 2016) - Norton, John D.
Abstract: Standard descriptions of thermodynamically reversible processes attribute contradictory properties to them: they are in equilibrium yet still change their state. Or they are comprised of non-equilibrium states that are so close to equilibrium that the difference does not matter. One cannot have states that both change and no not change at the same time. In place of this internally contradictory characterization, the term "thermodynamically reversible process" is here construed as a label for a set of real processes of change involving only non-equilibrium states. The properties usually attributed to a thermodynamically reversible process are recovered as the limiting properties of this set. No single process, that is, no system undergoing change, equilibrium or otherwise, carries those limiting properties. The paper concludes with an historical survey of characterizations of thermodynamically reversible processes and a critical analysis of their shortcomings. Highlights: Thermodynamically reversible processes carry contradictory properties. They are supposed to be in equilibrium yet still change their state. Their properties are really the limiting properties of a set of irreversible processes.